The Impact of Physical Screening on Position Selection and Performance in Smash Badminton Athletes - A Literature Review - Nimrot Manalu (Joska: Jurnal Isori Kampar, 2025)
Objectives: To systematically evaluate the relationship between physical screening assessments and their impact on position selection and smash performance in competitive badminton players. Methods: A comprehensive literature review was conducted across electronic databases including PubMed, SCOPUS, Web of Science, and sport-specific databases from January 2000 to March 2025. Search terms included combinations of "badminton," "smash," "performance," "screening," "position selection," and "physical assessment." Studies were included if they examined physical screening metrics, position selection factors, or smash performance parameters in badminton athletes. Results: Analysis of 37 eligible studies revealed strong associations between specific physical screening parameters and smash performance. Key physical attributes identified include shoulder rotational strength, upper limb power, lower extremity explosive strength, core stability, and trunk rotation capacity. Body positioning significantly influenced shuttlecock release angle and clearance height. Gender-specific differences were observed in smash velocity (98.7 m/s for males vs. 78.5 m/s for females) and technique, with females typically employing a "kick-through" rather than "two-footed jump" approach. Conclusion: Physical screening assessments provide valuable data for optimizing position selection and enhancing smash performance in badminton. Targeted assessments of shoulder internal rotation strength in the abducted position, trunk rotation capacity, and lower limb explosive power demonstrate the strongest correlation with smash performance. Implementation of sport-specific screening protocols can identify athlete strengths and weaknesses, informing individualized training programs and optimal court positioning strategies.